“Call Center” sebagai Alat Komunikasi Pemasaran di Abad ke-21 - Ratih Tresnati (MediaTor)
Call center is a part of contact center who responsible to serve customers. Call center relates corporate and targeted market. As communication media whose tasks are focused to serve the customers, call center receives and processes consumer expectations and hopes. The result can be processed as an opportunity for the corporate to expand its market and develop their products. Call center is believed could raise customer satisfactions by reduced service costs for each customer in long term action plan.